2022
DOI: 10.30699/jogcr.7.6.497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lactate Dehydrogenase and Gamma Glutamyl Transferase Among Pregnant Women with Hypertensive Disorders and Their Association with Disease Severity in Jimma Medical Center, Ethiopia

Abstract: Background & Objective: Pregnancy-induced hypertensive disorders (PIHD) are the main reasons for maternal and perinatal mortality, as they complicate 10% of pregnancies worldwide. Serum lactic acid dehydrogenase (LDH) and gamma-glutamyl transferase (GGT) are possible markers reflecting the occurrence of pregnancyassociated complications like preeclampsia and eclampsia. There is a paucity of data with conflicting results showing serum LDH and GGT on PIHD in Ethiopia. This investigation aimed to assess the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
0
1
Order By: Relevance
“…Furthermore, systolic and diastolic blood pressure showed independent association with serum LDH level in this study. This finding was consistent with a number of previous studies done on similar subjects (13,16,24,26,27).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, systolic and diastolic blood pressure showed independent association with serum LDH level in this study. This finding was consistent with a number of previous studies done on similar subjects (13,16,24,26,27).…”
Section: Discussionsupporting
confidence: 94%
“…Another research undertaken in India reported mean serum level of LDH to be 513.37 ± 203.44 and 261 ± 78.47 in preeclamptic and healthy controls, respectively. In addition, a study done in Ethiopia reported mean level of serum LDH in preeclamptic study groups to be 353 ± 132.8 which was slightly lower than the finding of the present study (8,24,25). This observed discrepancy might possibly be due to the lowering effects of antihypertensive drugs, which were being taken by some of our study subjects.…”
Section: Discussioncontrasting
confidence: 89%